Results of the inoperable and operable with aortic valve endocarditis - Huang, Jing-bin; Lu, Chang-chao; Du, Zhen-zong; Yang, Jian-rong; Li, Jun-jun (Frontiers in Cardiovascular Medicine, 2024)
Objectives To evaluate the results of the inoperable and operable with aortic valve endocarditis, focus on risk factors, significance, and management of destruction of the aortic annulus in aortic valve endocarditis. Methods The retrospective study was completed to investigate patients with aortic valve endocarditis undergoing cardiac surgery between January 2006 and November 2022 at our hospital. Results 512 patients were divided into group with destruction of the aortic annulus (n = 80) and without destruction of the aortic annulus (n = 432). There were 32 operative deaths (6.3%, 32/512). By univariate and multivariate analysis, destruction of the aortic annulus is found to be statistically significantly associated with in-hospital mortality (P < 0.001), prolonged mechanical ventilation time (mechanical ventilation time > 96 h, P = 0.018), early aortic paravalvular leak (P < 0.001), and 1-year mortality following cardiac surgery (P < 0.001), respectively. Conclusions In our study, destruction of the aortic annulus increases mortality and health care costs. Optimization of pre-, peri-, and postoperative factors can reduce mortality and morbidity in aortic valve endocarditis. Aortic root replacement could be recommended as the best practice choice for aortic valve endocarditis with periannular abscess and destruction of the aortic annulus.